Senescence induces fundamental changes in the secretome of mesenchymal stromal cells (MSCs): implications for the therapeutic use of MSCs and their derivates - Siraj, Yesuf; Galderisi, Umberto; Alessio, Nicola (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stromal cells (MSCs) are a heterogeneous population containing multipotent adult stem cells with a multi-lineage differentiation capacity, which differentiated into mesodermal derivatives. MSCs are employed for therapeutic purposes and several investigations have demonstrated that the positive effects of MSC transplants are due to the capacity of MSCs to modulate tissue homeostasis and repair via the activity of their secretome. Indeed, the MSC-derived secretomes are now an alternative strategy to cell transplantation due to their anti-inflammatory, anti-apoptotic, and regenerative effects. The cellular senescence is a dynamic process that leads to permanent cell cycle arrest, loss of healthy cells’ physiological functions and acquiring new activities, which are mainly accrued through the release of many factors, indicated as senescence-associated secretory phenotype (SASP). The senescence occurring in stem cells, such as those present in MSCs, may have detrimental effects on health since it can undermine tissue homeostasis and repair. The analysis of MSC secretome is important either for the MSC transplants and for the therapeutic use of secretome. Indeed, the secretome of MSCs, which is the main mechanism of their therapeutic activity, loses its beneficial functions and acquire negative pro-inflammatory and pro-aging activities when MSCs become senescent. When MSCs or their derivatives are planned to be used for therapeutic purposes, great attention must be paid to these changes. In this review, we analyzed changes occurring in MSC secretome following the switch from healthy to senescence status.